Contextual interactive animated video media development to promote environmentally relevant chemical equilibrium learning and improve students’ motivation - Clarisa, Galuh; Hidayah, Rusly (Education and Development Research, 2026)
The study was conducted to generate and validate an animated video that will impact students' understanding of chemical equilibrium and its context. They hoped not only that students would grasp the concepts but also that they would show some interest in the material. The researchers designed the research and evaluated the video using the ADDIE model. They selected thirty-four students from the grade and then followed this up with some questions to answer before and after watching the video. The video is not just valid; it is quite good at explaining chemical equilibrium to students. They scored the video 4.57, which means it is valid and has good content. The video was practical when the students viewed it; sixty-two-point nine seven percent of students reported the video as easy to use, and ninety-point eight eight percent considered it very helpful. The video works well because students are interacting with pictures of the environment for information about chemical equilibrium. This encourages students to relate what they are learning to the real world. By researching chemistry concepts, the findings of this research further inform more general strategies to inform students about principles to follow in other areas. Chemical equilibrium is one of the subjects it teaches, but this video uses environmental examples for easy understanding. Students are educated on chemical equilibrium and how important it is, tied to the environment around them.